Political connections and informed trading: Evidence from TARP - Ozlem Akin; Nicholas S. Coleman; Christian Fons-Rosen; José-Luis Peydró (Financial Management, 2019)
We study insider trading behavior surrounding the largest bank bailout in history: Troubled Asset Relief Program (TARP). In politically connected banks, insider buying during the pre-TARP period is associated with increases in abnormal returns around bank-specific TARP announcement; for unconnected banks, trading and returns are uncorrelated. Results hold across insiders within the same bank and are stronger for finance-related government connections. Through a Freedom of Information Act request, we obtained the previously undisclosed TARP funds requested; the ratio of received to requested funds correlates both with abnormal returns and insider buying behavior in connected banks.
Keywords: D72; G01; G21; G28; 330; bank bailouts; insider trading; political connections; political economy in banking; TARP